Papillary thyroid carcinoma with neck metastasis in a 6 year old child: A case report - Matin, MA; Sobhan, AKMA; Kabir, Md Shahjahan; Uddin, AKM Shaif; Razzak, Md Abdur; Azad, Md Abul Kalam; Khanam, Mohosana (Bangladesh Journal of Otorhinolaryngology, 2020)
Thyroid cancers account for 0.5-3.0% of all childhood malignancy. But these cancers are extremely rare in paediatric age group before the age of 6 years. Although the disease is biologically more aggressive in children when compared with adults, the prognosis is better in several series. We report and discuss a case of 6 years old child with papillary thyroid carcinoma, which is the youngest reported case in Bangladesh. Bangladesh J Otorhinolaryngol; April 2019; 25(1): 60-63